2019
DOI: 10.1590/s1984-29612019065
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of Cymbopogon citratus essential oil and its nanoemulsion on sheep gastrointestinal nematodes

Abstract: The anthelmintic resistance stimulated the search for strategies for controlling gastrointestinal nematodes, including the use of free essential oils or its nanoemulsion. This study evaluated the anthelmintic efficacy of Cymbopogon citratus essential oil (CcEO) and C. citratus essential oil nanoemulsion (CcEOn). Pysicochemical analyses were performed. The in vitro effect was determined using the egg hatch test (EHT) on Haemonchus contortus and in vivo effect was evaluated in sheep infected with gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
1
18
0
3
Order By: Relevance
“…Inhibition of H. contortus egg hatch was previously demonstrated by the EO of one O. basilicum cultivar and associated with methyl chavicol and linalool as major compounds of the EO tested (Castro et al, 2017). In the present study, the EOs from Napoletano, Genovese and Ararat cultivars showed the highest anthelmintic activity, and they also contain methyl chavicol and linalool, as major compounds (table 1) Citral, a natural combination of the isomers neral and geranial, has been shown to be effective against several nematodes, including H. contortus, both isolated and as the major compound of EO (Hierro et al, 2006;Macedo et al, 2019). A negative correlation between the citral concentration and efficacy was found when the results of all EO cultivars were analysed (P = 0.03), whereas isolated citral showed the best activity when tested alone (table 2).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Inhibition of H. contortus egg hatch was previously demonstrated by the EO of one O. basilicum cultivar and associated with methyl chavicol and linalool as major compounds of the EO tested (Castro et al, 2017). In the present study, the EOs from Napoletano, Genovese and Ararat cultivars showed the highest anthelmintic activity, and they also contain methyl chavicol and linalool, as major compounds (table 1) Citral, a natural combination of the isomers neral and geranial, has been shown to be effective against several nematodes, including H. contortus, both isolated and as the major compound of EO (Hierro et al, 2006;Macedo et al, 2019). A negative correlation between the citral concentration and efficacy was found when the results of all EO cultivars were analysed (P = 0.03), whereas isolated citral showed the best activity when tested alone (table 2).…”
Section: Discussionsupporting
confidence: 53%
“…Several cultivars of O. basilicum present EOs with linalool, methyl chavicol (estragol), citral and eugenol as its main constituents, in variable concentrations (Vieira & Simon, 2000; Pascual-Villalobos & Ballesta-Acosta, 2003; Sajjadi, 2006; Martins et al ., 2010; Ottai et al ., 2012). These compounds have been shown to have anthelmintic activity, isolated or in a mixture, and they are also present, in different concentrations, in several other EOs (Katiki et al ., 2017; Ferreira et al ., 2018; Macedo et al ., 2019). The standardization of efficient cultivars or the combination of natural compounds is extremally important to human and veterinary pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Cymbopogon citratus essential oil nanoemulsion was also shown to inhibit 97.1% of H. contortus larvae hatching; however, it was not effective when used in live sheep infected with gastrointestinal nematodes (Macedo et al ., 2019). Moreover, C. citratus essential oil reduced the H. contortus burden by 38.5% in Meriones unguiculatus (gerbils) treated with 800 mg kg −1 (Macedo et al ., 2019). Thus, compounds in C. citratus have a lethal effect on nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, C. citratus essential oil or decoction inhibited H. contortus egg hatching and larval development by 90–99% at concentrations of 0.62–10 mg mL −1 (Macedo et al ., 2015). Cymbopogon citratus essential oil nanoemulsion was also shown to inhibit 97.1% of H. contortus larvae hatching; however, it was not effective when used in live sheep infected with gastrointestinal nematodes (Macedo et al ., 2019). Moreover, C. citratus essential oil reduced the H. contortus burden by 38.5% in Meriones unguiculatus (gerbils) treated with 800 mg kg −1 (Macedo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation